Multisystem inflammatory syndrome, probably associated with SARS-CoV-2, complicated by thrombus in the right atrium, in a child - O. V. Usachova; O. V. Konakova; Ye. A. Silina; N. V. Vorobiova (Patologìâ)
Aim. Clinical case report of multisystem inflammatory syndrome, probably associated with COVID-19 and complicated by large thrombus in the right atrium in a child highlights the problems of monitoring, treatment, and the possibility of their solution.